Pseudomonas forestsoilum sp. nov. and P. tohonis biocontrol bacterial wilt by quenching 3-hydroxypalmitic acid methyl ester - Wang, Si; Hu, Ming; Chen, Huilin; Li, Chuhao; Xue, Yang; Song, Xinyue; Qi, Yuqing; Liu, Fan; Zhou, Xiaofan; Zhang, Lian-hui; Zhou, Jianuan (Frontiers in Plant Science, 2023)
Bacterial wilt caused by Ralstonia solanacearum ranks the second top important bacterial plant disease worldwide. It is also the most important bacterial disease threatening the healthy development of Casuarina equisetifolia protection forest. 3-hydroxypalmitic acid methyl ester (3-OH PAME) functions as an important quorum sensing (QS) signal regulating the expression of virulence genes in R. solanacearum, and has been regarded as an ideal target for disease prevention and control. To screen native microorganisms capable of degrading 3-OH PAME, samples of C. equisetifolia branches and forest soil were collected and cultured in the medium containing 3-OH PAME as the sole carbon source. Bacteria with over 85% degradation rates of 3-OH PAME after 7-day incubation were further separated and purified. As a result, strain Q1-7 isolated from forest soil and strain Q4-3 isolated from C. equisetifolia branches were obtained and identified as Pseudomonas novel species Pseudomonas forestsoilum sp. nov. and P. tohonis, respectively, according to whole genome sequencing results. The degradation efficiencies of 3-OH PAME of strains Q1-7 and Q4-3 were 95.80% and 100.00% at 48 h, respectively. Both strains showed high esterase activities and inhibited R. solanacearum exopolysaccharide (EPS) and cellulase production. Application of strains Q1-7 and Q4-3 effectively protects C. equisetifolia, peanut and tomato plants from infection by R. solanacearum. Findings in this study provide potential resources for the prevention and control of bacterial wilt caused by R. solanacearum, as well as valuable materials for the identification of downstream quenching genes and the research and development of quenching enzymes for disease control.